Development of the Forgiveness Schema in Adolescence - Girard, Michelle; University of Sophia-Antipolis (2012)
The study aims to chart the development of the willingness to forgive among adolescents, as a function of seven situational factors: Possibility of revenge, cancellation of harmful consequences, encouragement to forgive from parents and/or from close friends, social proximity with the offender, intent to harm, and presence of apologies. The participants were presented with 16 stories in which an adolescent committed a harmful act against another one. Each participant was asked to rate the degree of personal willingness to forgive in each case on a continuous scale. The effect of the cancellation of consequences factor was the strongest one, and it was stronger among younger adolescents than among older adolescents. The effect of the intent factor was the second strongest factor, and it was stronger among older adolescents than among younger adolescents. The effect of the encouragement factors was moderate (encouragement by friends), or small (encouragement by parents), and no age difference was observed. The effects of the revenge, apologies, and social proximity factors were always weak. An additive-type combination process was observed in each age group.